Linguistic Identity of Russians in the Latvian Lands in the Second Half of the 19th−Early 20th Centuries - Volkov, Vladislav (Forum for Linguistic Studies, 2025)
The purpose of this article is to present empirical material reflecting the processes of formation and reproduction of linguistic identity based on the Russian language and Russian culture among the Russian population of the Latvian lands that were part of the Russian Empire. The historical period chosen for scientific analysis in this article — the second half of the 19th and early 20th centuries — is extremely important for the processes of bourgeois modernization in Eastern Europe, accompanied by processes of nation-building. At the same time, the article critically addresses narratives prevalent in contemporary public consciousness and even academic research that claim that the processes of modernization of the social life of the Russian population in this region of Russia were reduced exclusively to problems of nation-building and the actualization of ethnic identity. The author of the article demonstrates that the appeal of Russians to the values of linguistic identity was linked to the need to consolidate Russian communal life in the Baltics. To a lesser extent, representatives of Russian society saw the dissemination of their linguistic identity as a means of distancing themselves from other ethnic groups. The article uses an analysis of academic literature and an extensive array of materials published in Russian newspapers and magazines in Riga, the largest city in the Baltic provinces of the Russian Empire during the period under review.